Лидар для измерения вертикального распределения озона в атмосфере - Долгий С. И. Сергей Иванович; Невзоров А. А. Алексей Алексеевич; Невзоров А. В. Алексей Викторович; Романовский О. А. Олег Анатольевич; Харченко О. В. Ольга Викторовна (2019, 2019)
Заглавие с титульного листа